BEST PRACTICES NILAI-NILAI KARAKTER MULTIKULTURAL DI PONDOK PESANTREN NGALAH, PASURUAN - Achmad Yusuf (Universitas Yudharta Pasuruan, 2019)
This research aims to uncover and describe the best practices of the multicultural character value of Pondok Pesantren Ngalah Pasuruan. The approach used is qualitative-naturalistic, with Case study type (case study). Data consists of primary and skunder data. The informant is determined through purposive sampling technique. Snowball sampling. Data collected 1) in-depth interviews, 2) participant observations and 3) documentation studies. Analysis of data using descriptive technique of interactive model L) data reduction, 2) data presentation and 3) withdrawal conclusion/verification. The results of this study concluded that Best practices the value of multicultural characters in Pesantren Ngalah, Pasuruan is: (1) The value of religious characters, (2) The value of the human character is a core value that grows other values include; (a) The character of caring and the students ' familiosity; (b) The value of the Brotherhood character, (c) the character of affection, (d) egalitarian/the line of doctrine; (3) inclusive-pluralist characters; The value of an inclusive-pluralist character (open accepts differences). (4) Character value tolerance (TASAMUH); Tolerance value of students, including; (a) Tolerance in interfaith Association, (b) to say greetings to Non Muslims, (c) Non Muslims enter the mosque. (5) Luwas and Luwes (moderate) character values; (6) Democratic character value, and (7) nationalist character value.